Nutrition affects insect susceptibility to Bt toxins - Deans, Carrie A.; Behmer, Spencer T.; Tessnow, Ashley E.; Tamez Guerra, Patricia; Pusztai Carey, Marianne; Sword, Gregory A. (2017)
Pesticide resistance represents a major challenge to global food production. The spread of resistance alleles is the primary explanation for observations of reduced pesticide efficacy over time, but the potential for gene-by-environment interactions (plasticity) to mediate susceptibility has largely been overlooked. Here we show that nutrition is an environmental factor that affects susceptibility to Bt toxins. Protein and carbohydrates are two key macronutrients for insect herbivores, and the polyphagous pest Helicoverpa zea self-selects and performs best on diets that are protein-biased relative to carbohydrates. Despite this, most Bt bioassays employ carbohydrate-biased rearing diets. This study explored the effect of diet protein-carbohydrate content on H. zea susceptibility to Cry1Ac, a common Bt endotoxin. We detected a 100-fold increase in LC50 for larvae on optimal versus carbohydrate-biased diets, and significant diet-mediated variation in survival and performance when challenged with Cry1Ac. Our results suggest that Bt resistance bioassays that use ecologically- and physiologically-mismatched diets over-estimate susceptibility and under-estimate resistance.